Determinism of Media Technology and Distortion of Siri’ Culture - Muhammad Qadaruddin; Wahyuddin Bakri; Jalihah Md Shah; Irlan Cahyadi; Andini Sasriani (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2023)
The rapid development of communication technology, particularly in social media platforms such as Facebook, TikTok, and Instagram, profoundly influences the entire human experience. The influence includes cultural shifts among adolescents, precisely distortions to the